Optimization of fractionation with membranes of antioxidant enzymatic hydrolysate of Californian red worm (Eisenia fetida) protein (2024)
ABSTRACT: Problem: Earthworm is a valuable source of biologically and pharmacologically active compounds, with applications in the treatment of various types of diseases; however, the main application they have been given is in the production of organic fertilizer. One of the alternatives for obtaining bioactive compounds is by means of enzymatic hydrolysis. Aim: This study proposes the optimization of the fractionation of the antioxidant enzymatic hydrolysate from Californian red worm (Eisenia fetida) protein. Methodology: For this purpose, the worms were separated and hydrolyzed using the enzyme Alcalase 2.4L for 4000s. The obtained hydrolysate was fractionated by means of a crossflow tangential ultrafiltration system, with a 3 kDa molecular weight cut-off ceramic membrane. A response surface design of the composite central factorial type was implemented to evaluate the effect of pH, transmembrane pressure, and flow factors on the response variables transmission, volume reduction factor (VRF) and permeate flow resistance. The transmissions focused on the antioxidant peptides, measured by three conventional methods such as TEAC, FRAP, ORAC, also known as TTEAC, TFRAP and TORAC, respectively. The evaluated resistances were the total resistance (Rtotal), fouling resistance (Rfouling), and gel resistance (Rgel). Result: The results showed that the three factors evaluated affect all the response variables either in their linear or quadratic terms or by some interaction. For each response variable, a mathematical model was obtained, with statistical significance and a non-significant lack of adjustment. The models obtained were used for a multi-objective optimization process in which transfers were maximized, and resistances were minimized. The efficiency of the optimum ultrafiltration process was 25 %. Conclusion: The neutral-alkaline pH is ideal for the ultrafiltration process of bioactive peptides, as it is where the highest transmissions of peptides with antioxidative capacity are found. Under optimal conditions, the 3 kDa membrane permeate was found to exhibit higher antioxidant capacity than the retentate and feed. Based on this, the fraction of less than 3 kDa emerges as a potential multifunctional ingredient, thanks to its antioxidant properties.